Arabic Speaking Skills Training through a Communicative Approach to Improve the Speaking Competence of Tenth Grade Students at Buranakarn Suksa Witya School Pattani, Thailand - Nurul Zuhriyah; Sri Wahyuningsih; Novi Ulfa Safitri (Abdimas Indonesian Journal, 2026)
Maharah kalam refers to speaking skills in the Arabic language that require clarity, fluency, and accuracy in conveying ideas and feelings orally. This skill is considered one of the primary goals of language learning because through speaking, individuals are able to interact, engage in dialogue, and express themselves communicatively in daily life. The communicative approach is a language teaching method that emphasizes students’ ability to communicate effectively and contextually rather than merely mastering grammatical structures. This training program aimed to strengthen the Arabic maharah kalam (speaking skills) of tenth-grade students at Buranakarn Suksa Witya School, Pattani, Thailand, through a communicative approach. The main problems faced by the students were: a) limited active vocabulary, b) lack of confidence in speaking, and c) learning activities that still focused on memorizing vocabulary without communicative context. The objectives of this community service program were: 1) to implement maharah kalam training through a communicative approach for students at Buranakarn Suksa Witya School, Pattani, Thailand; and 2) to improve the Arabic speaking ability of the students.The implementation method used practice-based training, including contextual vocabulary introduction, pronunciation exercises, thematic dialogues, and real-life situation simulations. The results of the activity showed that: 1) the implementation of maharah kalam training for students at Buranakarn Suksa Witya School, Pattani, Thailand was carried out successfully in accordance with the communicative approach; and 2) the training proved effective in increasing students’ active participation, speaking confidence, and ability to construct simple utterances in Arabic.